Noninvasive prenatal testing: a survey of young (future) parents in Flanders. (January 2018) - Borry, Pascal; Favaretto, Maddalena; Batthyany, Ann; Boey, Eline; Van Tongerloo, Sophie; Dooms, Marc; Huys, Isabelle
Aim: To explore the opinions of young (future) parents toward noninvasive prenatal testing.Materials & methods: A questionnaire was administrated.Results: A total of 1006 surveys were completed by visitors of 40 secondhand clothing fairs spread equally over Flanders (Belgium). The respondents expressed an overall positive opinion toward the use and implementation of a noninvasive prenatal test (NIPT). Most respondents claimed that they would test their unborn child for genetic disorders, even if this was to result in a termination of the pregnancy.Conclusion: The participants agreed nearly unanimously that NIPT must be offered to pregnant women with an increased risk of having a child with a genetic disorder, but they were also positive about extending NIPT screening to all pregnant women.